Environmental Inequality in Austria: Sociodemographic Disparities in Perceived Environmental Quality - Durstmüller, Felix (Wirtschaft und Gesellschaft, 2022)
This quantitative study investigates the relationship between perceived environmental conditions (air pollution, noise, extreme heat, access to green space) and socioeconomic status in Austria. Building upon the work of Baud and Wegscheider-Pichler (2019) and integrated into the theoretical framework of environmental justice, it aims to enrich the empirical body of literature on environmental inequality in Austria by adding the subjective perspective of affected individuals in order to highlight individual vulnerabilities and capability to adapt. Data from the Austrian Microcensus 2019, a large-scale population-based survey, is used. In this survey, information on perceived exposure to adverse environmental conditions was collected from a total of 7,021 respondents. To analyse the association between subjective exposure and sociodemographic characteristics, binomial and ordinal logistic regression models are applied. The findings suggest that lower income is associated with a lower perception of overall environmental quality and a higher level of perceived exposure to air pollution. A correlation between income and level of noise disturbance is only present in Vienna, and no relationship between income and perceived heat stress can be identified. However, in almost all categories of adverse environmental impacts, women feel more affected than men, and housing conditions are significantly related to perceived noise annoyance. Mixed results are found regarding the role of migration background. While individuals with migration backgrounds report higher personal exposure to air pollution, they rate the overall environmental quality as better than people without migration backgrounds. In line with other empirical studies, the results confirm that exposure to adverse environmental conditions is distributed unequally across society in Austria. To address these inequalities, concerns of environmental justice should be integrated into public discourse and policymaking.